2017
DOI: 10.1007/s13361-017-1765-1
|View full text |Cite
|
Sign up to set email alerts
|

TOF MS Investigation of Nickel Oxide CVD

Abstract: NiO layers were deposited by metal-organic chemical vapor deposition using bis-(ethylcyclopentadienyl) nickel (EtCp)Ni and oxygen or ozone. As a continuation of kinetic study of NiO MOCVD the gas-phase, transformations of (EtCp)Ni were studied in the temperature range of 380-830 K. Time of reactions corresponding to the residence time of the gas stream in hot zone of the reactor was about 0.1 s under conditions studied. The interaction of (EtCp)Ni with oxygen started at 450 K and its conversion rate reached th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…While recent advancements in printed electronics and additive manufacturing technologies have provided a new paradigm in scalable manufacturing of many of such glucose sensors, the desired functional material for printing still needs to be prepared in the form of inks and pastes made of suspended nano- and microparticles. The synthesis of these materials often relies on time-consuming chemical synthesis processes including solvothermal/hydrothermal processes, , sol–gel, chemical bath deposition, chemical and physical , vapor deposition, electrochemical deposition, microwave-assisted approaches, and electrospinning . Apart from material synthesis challenges, glucose sensors often require printing of multilayers which faces different technical manufacturing challenges, including the need of multiple curing/drying steps between each printed layers and also the high risk of ineffective contact/bonding between printed layers …”
Section: Introductionmentioning
confidence: 99%
“…While recent advancements in printed electronics and additive manufacturing technologies have provided a new paradigm in scalable manufacturing of many of such glucose sensors, the desired functional material for printing still needs to be prepared in the form of inks and pastes made of suspended nano- and microparticles. The synthesis of these materials often relies on time-consuming chemical synthesis processes including solvothermal/hydrothermal processes, , sol–gel, chemical bath deposition, chemical and physical , vapor deposition, electrochemical deposition, microwave-assisted approaches, and electrospinning . Apart from material synthesis challenges, glucose sensors often require printing of multilayers which faces different technical manufacturing challenges, including the need of multiple curing/drying steps between each printed layers and also the high risk of ineffective contact/bonding between printed layers …”
Section: Introductionmentioning
confidence: 99%
“…These Ni‐rich films also showed resistive switching behavior, though the initial resistivity values were not reported. Kondrateva et al showed excess oxygen in their NiO x films deposited using ethylcyclopentadienyl nickel (Ni[EtCp] 2 ) and O 2 + O 3 , with Ni/O ratio of 0.85, 61 but no electrical properties were reported.…”
Section: Chemical Deposition Of Nickel Oxide Thin Filmsmentioning
confidence: 99%
“…NiO x thin films have also been successfully applied as hole transporting layers (HTLs) in organic and perovskite solar cells [ 6 , 7 , 8 , 9 , 10 ], and in inorganic and perovskite light-emitting diodes (LEDs) [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Various methods can be used to prepare NiO thin films, such as RF and DC magnetron sputtering [ 4 , 19 , 20 ], electron-beam evaporation [ 21 ], pulsed laser deposition [ 22 , 23 ], atomic layer deposition [ 24 ], metal-organic chemical vapor deposition [ 25 ], chemical bath deposition [ 26 ], spin coating [ 27 ], sol-gel process [ 28 ], SILAR [ 29 ], and Spray Pyrolysis (SP) [ 30 , 31 ]. Among all these methods, the SP technique has the advantage of being easy and economical because it does not need high vacuum equipment and offers the possibility for large area deposition.…”
Section: Introductionmentioning
confidence: 99%